RELASI AGAMA DAN SAINS DALAM PANDANGAN MEHDI GOLSHANI - Hidayatullah, Syarif (Jurnal Filsafat "WISDOM", 2018)
The Research aims to know: (a) How about Mehdi Golshani’s thoughts   on relationship between science and religion?, and, (b) How about relevancy Mehdi Golshani’s thoughts  for developing of  science and religion scientifically. So, the material object of the research is Golshani’s thoughts   on relationship between science and religion that is studied with using epistimology as it’s the formal object.  Results of the research that: firtsly, Golshani used terms of   “the sacred sciences” and “the secular sciences” for understanding to relationship between the science and the religion. Then, his idea on “the sacred sciences” developed by him becomes “Islamic Science”.  He defines that the “Islamic Science” is a kind of science that has   a weltanschauung which it based on the Quran values. Here, Golshani stresses on an importance to develop the Quran epistemology in Moslems society in modern era now.  Secondly, to create ideal   expectations in the relationship between science and religion and its benefits for humankind and harmony in the universe, Mehdi Golshani’s thoughts and implementable offers, especially  for developing  natural sciences in the Moslems society, are an urgent thing and properly considerable.Keywords: “the sacred sciences”, the “Islamic Science”, the Quran epistemology